Reducing vulnerability to hydro-meteorological extremes in Africa. A qualitative assessment of national climate disaster management policies: accounting for heterogeneity - Tall, Arame; Patt AG; Fritz, Steffen (Elsevier, 2013)
In Africa, hydro-meteorological disasters (HMDs) have hit with increasing frequency and magnitude in recent years, with detrimental impacts on local livelihoods. African countries display a patchwork of national policies and institutional frameworks to address these rising HMDs. This paper examines the heterogeneity that exists within Africa′s institutional arrangements for climate-related disaster risk management, and introduces a three-partite policy classification that ranks each country as one of three disaster management policy types: the ‘Unprepared Firefighters′ (whose response to disasters is late, delayed and ineffective), the ‘Prepared Firefighters′ (for the most part effective disaster responders) and the ‘Disaster Averters′ (who experienced a paradigm shift and moved focus away from the hazard itself towards a reduction of the underlying risk factors that cause disasters). Through extensive data mining, interviews and qualitative country assessments, we map where African countries lie on this spectrum of effective climate-related disaster risk management. We find that African countries lay at different levels on the spectrum of effective disaster risk management. Across Africa, countries display differential progress in achieving the Hyogo Framework for Action goals and great variation and heterogeneity exists from country to country, one that calls for a concomitant heterogeneity in aid programs and initiatives meant to support comprehensive disaster risk reduction and climate change adaptation (DRR–CCA) in Africa. In closing, this paper suggests ways to support African countries′ efforts towards effective disaster risk management and planning. It offers a qualitative method to continually assess developing countries′ progress in achieving the Hyogo Framework for Action goals, one that straddles top-down country self-reporting and bottom-up civil society assessment.